Comparison of outcomes following minimally invasive and open posterior cervical foraminotomy: description of minimally invasive technique and review of literature - Platt, Andrew (J Spine Surg, 2020)
Although minimally invasive posterior cervical foraminotomy (MIS-PCF) is frequently employed in the treatment of cervical radiculopathy, there are very few studies directly comparing outcomes between MIS-PCF and open posterior cervical foraminotomy and between MIS-PCF and percutaneous endoscopic (full-endoscopic) posterior cervical foraminotomy (FE-PCF). This study includes a description of technique and systematic review of literature and analysis of clinical studies comparing outcomes between MIS-PCF and open posterior cervical foraminotomy and between MIS-PCF and FE-PCF. Six comparative studies, including one randomized controlled trial were included in analysis. Average operative time ranged from 60.5 to 171 minutes in the open group and 77.65 to 115 minutes in the MIS group. Mean intraoperative blood loss ranged from 43.5 to 246 cc in the open group and 42 to 138 cc in the MIS group. Average postoperative length of stay ranged from 58.6 to 304.8 hours in the open group and 20 to 273.6 hours in the MIS group. Two studies reported significantly increased VAS-N (Neck) scores postoperatively in patients undergoing open cervical foraminotomies, however both studies reported that the differences lost statistical significance with longer follow-up. There were no significant differences in complications or reoperations between open and MIS groups. One retrospective cohort study was included in analysis that compared MIS-PCF and FE-PCF. Postoperatively at 24 months, mean NDI and VAS-N were significantly lower after FE-PCF than MIS-PCF. There was no significant change in VAS-A (Arm) between the two groups. Direct comparative studies between MIS-PCF and open cervical foraminotomy are limited in number. Although, there is a significant heterogeneity in studies comparing open and MIS-PCF there appears to be a trend of decreased hospital length of stay and postoperative analgesic usage in the minimally invasive cohort.